The Dark Side of Digital Financial Inclusion: Evidence on Risk-Taking Behavior in Chinese Commercial Banks - Weimin Chen; Chang Liu; Lin Zhang (Ilmu Inovasi Nusantara, 2026)
The rapid development of digital inclusive finance has brought profound transformations to the financial industry, particularly affecting commercial banks, which are its core institutions. The increasing accessibility and efficiency of digital financial services have significantly pressured traditional banking activities, particularly in deposit mobilization and lending. This disruption has led to a decline in net interest margins, thereby weakening bank profitability. In response, commercial banks may be incentivized to pursue higher-risk investment strategies to preserve their franchise value, thereby increasing their overall risk-taking. Accordingly, this study aims to examine the impact of digital inclusive finance on the risk-taking levels of Chinese commercial banks. This research adopts a quantitative approach, using panel data from Chinese commercial banks over a specified period. The analysis employs regression models to examine the relationship between the development of digital inclusive finance and bank risk-taking, while controlling for relevant variables, including bank size, liquidity, and operational efficiency. The findings indicate that digital inclusive finance has a significant positive effect on commercial banks' risk-taking behavior. The compression of profit margins compels banks to seek alternative sources of income through higher-risk investment instruments. Furthermore, the effect is more pronounced among banks with lower levels of digital adaptation. The implications of this study highlight the necessity for well-structured digital transformation strategies and strengthened financial regulation. Commercial banks are encouraged to pursue sustainable innovation while adhering to prudential principles, and regulators are urged to design adaptive policies to ensure financial stability and an effective risk prevention and control system